2016
DOI: 10.1080/08869634.2016.1201633
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of parents/guardians about nocturnal bruxism in children and adolescents

Abstract: Guardians have a widespread ignorance about the causes and consequences of sleep bruxism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
2
8
1
1
Order By: Relevance
“…With regard to the etiology, the majority of interviewees (74.8%) were unable to say what led to bruxism. Seventeen interviewees (16.5%) associated bruxism with emotional factors, which is in agreement with findings described in similar studies 13 , 14 , although the percentage of interviewees who considered emotional aspects to be the causal factor of bruxism was considerably higher (63.8%) in the study by Serra-Negra et al 13 . Regarding the mystical aspects, 20.4% of the interviewees in the study Serra-Negra et al 13 believed that witchcraft was the probable cause of bruxism, whereas only one caregiver (1%) in the present study attributed the parafunctional habit to this cause.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With regard to the etiology, the majority of interviewees (74.8%) were unable to say what led to bruxism. Seventeen interviewees (16.5%) associated bruxism with emotional factors, which is in agreement with findings described in similar studies 13 , 14 , although the percentage of interviewees who considered emotional aspects to be the causal factor of bruxism was considerably higher (63.8%) in the study by Serra-Negra et al 13 . Regarding the mystical aspects, 20.4% of the interviewees in the study Serra-Negra et al 13 believed that witchcraft was the probable cause of bruxism, whereas only one caregiver (1%) in the present study attributed the parafunctional habit to this cause.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted in the city of Rio de Janeiro (southeastern Brazil), 33.6% of the caregivers of children with bruxism reported that they did not seek help and 54.5% of the participants did not answer the question. In the present investigation, the professional most consulted was a dentist (10.4%), followed by a physician and psychologist (0.7% of the participants for each of these two specialists) 14 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The current scientific evidence about bruxism in children present various aspects that are still inconclusive, however, they already indicate that SB is more prevalent in younger children, with worse sleep quality and with anxious 8,9 or nervous behaviors 6,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on the formula for the estimation of the population proportion with correction for a finite sample, using a parent-reported bruxism prevalence of 23.1% 6 , a 95% confidence level, an acceptable rate of error of 5% and a total of 500 children in this age group at the pediatric dentistry service. The minimum sample size was 176 children and 20% was added to compensate for possible dropouts, resulting in 212 children.…”
Section: Study Design and Samplementioning
confidence: 99%